Marine Square, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A view of Marine Square which was renamed Independence Square in 1962.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Plazas--Trinidad and Tobago; Buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Trees--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Promenades (Pedestrian areas)--Trinidad and Tobago; Pedestrian areas--Trinidad and Tobago; Marine Square (Port of Spain); Independence Square (Port of Spain)